2011
DOI: 10.1007/s00520-011-1300-z
|View full text |Cite
|
Sign up to set email alerts
|

What are the perceived needs and challenges of informal caregivers in home cancer palliative care? Qualitative data to construct a feasible psycho-educational intervention

Abstract: Considering the time pressures and restricted caregiver time, the intervention should be brief and should aim to enhance their visibility as service recipients, patient-specific information giving, preparation for their role, and emotional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 26 publications
2
71
1
2
Order By: Relevance
“…While previous studies have found that HCAs supporting palliative care work in the community regard the provision of emotional support as a key aspect of their role (Clark et al 2000;Devlin & McIlfatrick 2010;Ingleton et al 2011), little research has considered the experiences of family carers in receiving such support. Given that there is widespread awareness of the potential emotional burden on family care givers caring for a patient at home (Harding et al 2012;Jack & O'Brien 2010) and recent research from New Zealand suggests there is still work to be done in improving the 'interface' between health professionals and family carers (McPherson et al 2014), we highlight the importance of researching family carers who receive emotional support, and how this affects their experiences of caring for patients at the end-of-life.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have found that HCAs supporting palliative care work in the community regard the provision of emotional support as a key aspect of their role (Clark et al 2000;Devlin & McIlfatrick 2010;Ingleton et al 2011), little research has considered the experiences of family carers in receiving such support. Given that there is widespread awareness of the potential emotional burden on family care givers caring for a patient at home (Harding et al 2012;Jack & O'Brien 2010) and recent research from New Zealand suggests there is still work to be done in improving the 'interface' between health professionals and family carers (McPherson et al 2014), we highlight the importance of researching family carers who receive emotional support, and how this affects their experiences of caring for patients at the end-of-life.…”
Section: Introductionmentioning
confidence: 99%
“…Caring for a cancer patient affects the caregiver's communication patterns, job performance, and social roles and presents her with seemingly complex challenges. According to previous qualitative studies conducted on the subject, caregiver expressed a wide range of needs, including preparation for the caring role, being noticed by professional care providers, receiving clear information about the patient's condition and emotional support . In a study conducted by Hurding, Epiphaniou et al., families were also faced with challenges such as uncertainty, distress due to witnessing the progress of the disease, daily financial problems, shortage of time, sleep problems and health issues .…”
Section: Introductionmentioning
confidence: 99%
“…all 13 studies include informal caregivers (family or close friends) of patients with severe disease (cancer or not) in palliative condition as participants, followed by teams of PC or Intensive Care units (ICU's). Six studies intended to examine the influence of gender, skills, experiences and needs of carers in their home environment and two studies tried to do it in a hospital setting [6,[14][15][16][17][18]. One study reported caregivers experiences with ventilated patients at home, and other showed the evidence of caring for patients with Amyotrophic Lateral Sclerosis (ALS) [12,19] Four studies did not specify the setting of care where the patient was during the data collection [9,13,16,17,[20][21][22], and four did not make reference to the fact that the patient was followed or not by a PC team.…”
Section: Resultsmentioning
confidence: 99%
“…Reported that 90% of the care of dependent patients are provided by family carers and this means being available day and night (24 hours/day), supporting the patient, meeting and reducing their suffering [16,23]. The primary caregiver, who is normally the nearest person, usually provides physical, psychological, social and spiritual care, aiming to promote the well-being of the patient, relatives and friends, allowing the patient to be cared for at home, and also contributing to cost reduction in health [3,15]. In the articles included in this systematic review, some caregivers who were not supported by health care teams often lost control of the situation, which was perceived as a negative experience [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation